Pengaruh Kepuasan Kerja, Motivasi Kerja dan Komitmen Afektif terhadap Kinerja Karyawan - Narwadan, Rosario (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study aims to prove whether job satisfaction, work motivation, and affective commitment affect employee performance.. The study took samples of employees who worked at the Seira Wermaktian Health Center. The sampling technique used total sampling. Data collection was carried out by sending questionnaires via personal chat or via email in the form of google form to puskesmas employees. The number of questionnaires processed is 45 questionnaires. The data analysis used multiple linear regression analysis. The results of this study indicate that job satisfaction, work motivation, and affective commitment partially have a positive effect on employee performance.